2021
DOI: 10.1186/s12871-021-01472-w
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic management in cesarean delivery of women with placenta previa: a retrospective cohort study

Abstract: Background The incidence of placenta preiva is rising. Cesarean delivery is identified as the only safe and appropriate mode of delivery for pregnancies with placenta previa. Anesthesia is important during the cesarean delivery. The aim of this study is to assess maternal and neonatal outcomes of patients with placenta previa managed with neuraxial anesthesia as compared to those who underwent general anesthesia during cesarean delivery. Methods A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…As in our previous review [ 4 ], we included observational studies (cross-sectional, cohort studies, and case-control) on placenta previa among pregnant women meeting the clinical diagnostic criteria [ 26 , 27 ] conducted in mainland China, providing they reported the prevalence or incidence of placenta previa. We excluded meeting abstracts; case reports and case series; poster presentations; and articles we could not access or that had incomplete data.…”
Section: Methodsmentioning
confidence: 99%
“…As in our previous review [ 4 ], we included observational studies (cross-sectional, cohort studies, and case-control) on placenta previa among pregnant women meeting the clinical diagnostic criteria [ 26 , 27 ] conducted in mainland China, providing they reported the prevalence or incidence of placenta previa. We excluded meeting abstracts; case reports and case series; poster presentations; and articles we could not access or that had incomplete data.…”
Section: Methodsmentioning
confidence: 99%
“…Data for the study was obtained from a retrospective cohort study of women with placenta previa at our hospital from January 2014 to June 2019. Approximately 13000 babies are born annually in this university-based tertiary medical center [ 24 , 25 ]. All participants with placenta previa who had blood type and delivery information were included.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, a study revealed a neonatal mortality rate of 10.7 per 1,000 births in previa cases, contrasting with 2.5 per 1,000 in other pregnancies (relative risk: 4.3; 95% confidence interval: 4.0, 4.8) [ 26 , 27 ]. Additionally, perinatal mortality rates are elevated in placenta previa, with one study reporting a rate of 81 per 1,000 births [ 3 ]. The heightened risk of neonatal morbidity and mortality stems from various factors, including preterm birth, low birth weight, birth asphyxia, and neonatal sepsis [ 28 ].…”
Section: Reviewmentioning
confidence: 99%
“…Maternal and perinatal outcomes in placenta previa are of paramount importance due to the potential for significant morbidity and mortality for both the mother and the fetus. Maternal complications may include severe hemorrhage, placenta accreta spectrum (PAS) disorders, and the need for emergency cesarean section, which can lead to adverse outcomes such as hysterectomy or even maternal death [ 3 ]. Similarly, perinatal complications such as preterm birth, intrauterine growth restriction (IUGR), and neonatal morbidity and mortality are common in pregnancies complicated by placenta previa, highlighting the critical need for effective management strategies [ 4 ].…”
Section: Introductionmentioning
confidence: 99%